Engaging Multiple Stakeholders in Environmental Education for Waste Management in Pangalengan Tourism Sites: The Case of Warnasari Village - Dudi Darmawan; Edy Wibowo; Heritiana Bethaningtyas (Jurnal Inovasi Sains dan Teknologi Untuk Masyarakat, 2025)
Warnasari Village, located in Pangalengan District, Bandung Regency, is a growing natural tourism destination with significant economic potential. However, the increasing number of visitors has led to various environmental challenges, particularly related to waste management and maintaining order in tourist areas. Limited supporting facilities and the low awareness of both tourists and local residents regarding environmental cleanliness have contributed to waste accumulation and reduced environmental quality. To address these issues, the Smart Science and Technology Study Program of Telkom University implemented a community service program in collaboration with the Warnasari Village Government and the Pangalengan Police Sector. This program focuses on strengthening environmental education through awareness campaigns, the provision of segregated waste bins, and the active involvement of local communities. Activities include educational workshops, the use of visual media, installation of waste facilities at strategic points, and outreach to schools and community groups. This multi-stakeholder collaboration aims to enhance community capacity and promote sustainable tourism behavior. The results indicate positive responses from residents and visitors, particularly in terms of material clarity, delivery methods, and the program’s potential sustainability. This collaborative model is expected to be replicable in other tourism areas facing similar environmental issues, supporting improved environmental governance through community-based participation.